1977
DOI: 10.1177/25.1.556750
|View full text |Cite
|
Sign up to set email alerts
|

Cytofluorometric quantitation of 5-hydroxytryptamine in mast cells: an improved technique for the formaldehyde condensation reaction.

Abstract: A simple technique for the condensation of cellular 5-hydroxytryptamine (5-HT) with formaldehyde gas is described. The technique, which is especially suited for quantitative cytofluorometric studies, involves the generation of formaldehyde gas from dry paraformaldehyde in a closed reaction vessel with the addition of a measured quantity of water. The fluorescence yield of 5-HT was tested at various humidities. Optimal results were obtained with the addition of 100 mg water to a 1000 ml reaction vessel containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1978
1978
1983
1983

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Previous studies have shown that the fluores cent formaldehyde reaction (13) can be used for specific and precise quantifica tion of 5-HT both in mast cells and in individual mast cell granules (12,19). To facilitate quantitation, we used mast cells with increased fluorescence intensity due to induced accumulation of 5-HT (12,13,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the fluores cent formaldehyde reaction (13) can be used for specific and precise quantifica tion of 5-HT both in mast cells and in individual mast cell granules (12,19). To facilitate quantitation, we used mast cells with increased fluorescence intensity due to induced accumulation of 5-HT (12,13,19).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitation o f 5-HT and Heparin 5-HT was quantitated after formaldehyde treatment according to Falck et al (15) with a modified and standardized technique as described previously (13). Heparin was quantitated with berberine binding after fixation in ethanol-acetic acid as described pre viously (11).…”
Section: Preparation O F Mast Cell Granulesmentioning
confidence: 99%
“…fluorescence, according to Falck et al (1962), and as described pre viously [Enerback et al, 1977b). Heparin and 5-HT release was cal culated as the percentage decrease in fluorescence intensity of mast cells incubated with polymyxin B in relation to control cells incu bated without polymyxin B.…”
Section: Microscopic Fluorometrymentioning
confidence: 99%
“…5-HT was quantitated with the fluorescentformaldehyde technique [12,15]. Heparin was quantitated by berberine binding [10].…”
Section: Quantitation Of 5-ht and Heparinmentioning
confidence: 99%
“…By combining this method with the standard ized fluorescent formaldehyde reaction for 5-hydroxytryptamine (5-HT) [12] the con tent of both an amine and a suggested ma trix component in mast cell granules can be quantitated cytofluorometrically under dif ferent experimental conditions.…”
Section: Introductionmentioning
confidence: 99%